Standard Care Versus Awake Prone Position in Adult Nonintubated Patients With Acute Hypoxemic Respiratory Failure Secondary to COVID-19 Infection—A Multicenter Feasibility Randomized Controlled Trial. (August 2021) - Jayakumar, Devachandran; Ramachandran, DNB, Pratheema; Rabindrarajan, DNB, Ebenezer; Vijayaraghavan, MD, Bharath Kumar Tirupakuzhi; Ramakrishnan, AB, Nagarajan; Venkataraman, AB, Ramesh
Rationale: The feasibility and safety of awake prone positioning and its impact on outcomes in non-intubated patients with acute respiratory distress syndrome secondary to COVID-19 is unknown. Results of the observational studies published during this pandemic have been conflicting. In this context, we conducted a multi-center, parallel group, randomized controlled feasibility study on awake prone positioning in non-intubated patients with COVID-19 pneumonia requiring supplemental oxygen. Methods: 60 patients with acute hypoxic respiratory failure secondary to COVID-19 pneumonia requiring 4 or more liters of oxygen to maintain a saturation of ≥92% were recruited in this study. Thirty patients each were randomized to either standard care or awake prone group. Patients randomized to the prone group were encouraged to self-prone for at least 6 hours a day. The primary outcome was the proportion of patients adhering to the protocol in each group. Results: In the prone group, 43% (13 out of 30) of patients were able to self-prone for 6 or more hours a day. In the supine group, 47% (14 out of 30) were completely supine and 53% spent some hours in the prone position, but none exceeded 6 hours. There was no significant difference in any of the secondary outcomes between the 2 groups and there were no adverse events. Conclusions: Awake prone positioning in non-intubated patients with acute hypoxic respiratory failure is feasible and safe under clinical trial conditions. The results of our feasibility study will potentially help in the design of larger definitive trials to address this key knowledge gap.